Regional Economic Outlook, April 2015, Sub-Saharan Africa : Navigating Headwinds. (Regional Economic Outlook, 2015)
The sharp decline in oil and other commodity prices have adversely impacted sub-Saharan Africa. Nevertheless, the region is projected to register another year of solid economic performance. In South Africa, however, growth is expected to remain lackluster, while in Guinea, Liberia, and Sierra Leone the Ebola outbreak continues to exact a heavy economic and social toll. This report also considers how sub-Saharan Africa can harness the demographic dividend from an unprecedented increase in the working age population, as well as the strength of the region's integration into global value chains.